2003
DOI: 10.1002/bit.10745
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of central metabolic fluxes in the facultative methylotroph methylobacterium extorquens AM1 using 13C‐label tracing and mass spectrometry

Abstract: The metabolic fluxes of central carbon metabolism were measured in chemostat-grown cultures of Methylobacterium extorquens AM1 with methanol as the sole organic carbon and energy source and growth-limiting substrate. Label tracing experiments were carried out using 70% (13)C-methanol in the feed, and the steady-state mass isotopomer distributions of amino acids derived from total cell protein were measured by gas chromatography coupled to mass spectrometry. Fluxes were calculated from the isotopomer distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 46 publications
3
46
1
Order By: Relevance
“…This step was designed to avoid dilution of isotope abundance caused by assimilation of naturally CO 2 via carboxylation reactions of the bacteria. [43] After autoclave, 13 C-labeled methanol was added in the medium to a final concentration of 1% (v/v). Frozen stock of M. salsuginis sp.…”
Section: Methodsmentioning
confidence: 99%
“…This step was designed to avoid dilution of isotope abundance caused by assimilation of naturally CO 2 via carboxylation reactions of the bacteria. [43] After autoclave, 13 C-labeled methanol was added in the medium to a final concentration of 1% (v/v). Frozen stock of M. salsuginis sp.…”
Section: Methodsmentioning
confidence: 99%
“…The following antibiotic concentrations were used: kanamycin, 100 g/ml; rifamycin, 50 g/ml; and tetracycline, 10 g/ml. To test the metal-dependent expression of FDHs, a similar medium was used in which molybdenum was omitted and molybdenum, tungsten, or both were added, as appropriate, at 0.3 to 3 M. Chemostat cultivation was performed in a bench-top fermentor essentially as previously described (5,21). The methanol concentration in the feed was 25 mM for the wild type and quadruple mutant A and either 25 or 45 mM for the triple-FDH mutant, and dilution rates were 0.1 h Ϫ1 unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…The organism has been well studied (Anthony 1982;Chistoserdova et al 1998;Korotkova et al 2002;Van Dien et al 2003;Chistoserdova et al 2004), and recently, a stoichiometric model of its central metabolism was published (Van Dien and Lidstrom 2002). Using Step 3 of OptStrain, we identified that only a single reaction needs to be introduced into the metabolic network of M. extorquens to enable hydrogen production.…”
Section: Extorquens Am1mentioning
confidence: 99%